Options to Extend Medicare’s Trust Fund: Lessons From Japan’s Statutory Health Insurance - Jared Lane K. Maeda PhD, MPH (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2022)
Medicare’s Hospital Trust Fund is projected to become insolvent sometime during 2028 and there will be insufficient funds to cover the costs of beneficiaries’ care if reforms are not made before then. Many options have been proposed on ways to extend the trust fund’s solvency. Some proposals focus on controlling costs and other proposals include options for raising revenues. A fresh perspective on this policy dilemma may arise by considering Japan’s statutory health insurance (SHI) and its financing mechanisms. Japan could be a useful model because it has an older population and it is facing similar fiscal challenges before Medicare. Japan could offer some useful perspectives from its cost containment efforts to extend Medicare’s solvency.